Electroencephalographic study of real-time arithmetic task recognition in learning disabilities children - Sittiprapaporn, Phakkharawat; Chang, Shao-Chin (Asian Journal of Medical Sciences, 2018)
Background: Mathematics form is universally understood in modern society. It is natural to ask whether there is neurophysiological evidence for putative cognitive components of the task and the practice in mental arithmetic will lead to a detectable transition in primary locus of brain activity. Aims and Objectives: The purpose of this study was to determine the effect of real-time arithmetic recognition task for cognitive performance and electroencephalographic activities. Materials and Methods: While practicing the real-time arithmetic recognition task named SpeedMath developed by NeuroSky, Inc., electroencephalographic activities were also recorded by using the commercial lightweight electroencephalographic device, Mindwave Mobile, NeuroSky, Inc. Eight participants included learning disabilities children participating in this study. All participants were instructed and trained to practice the simple the arithmetic recognition task which included arithmetic and mathematic skills. Results: The results showed that both alpha and beta frequency bands were increased with statistically significant at the 0.05 level. Conclusions: The real-time arithmetic recognition task might improve the real-time arithmetic recognition task and performance. Asian Journal of Medical Sciences Vol.10(1) 2019 43-46